Brand Extension Evaluation in Esports: A Case Study of the NBA and NBA2K League - Glynn M McGehee; Beth A. Cianfrone; Jackson Sears (Journal of Applied Sports Management, 2023)
Professional sport leagues have created esport leagues and teams, which serve as brand extensions (e.g., NBA and NBA 2K League). These brand extensions can benefit the professional sports team brand by reaching various audiences in a different product category. The purpose of this study was to examine a traditional sport entity’s (NBA franchise) esport brand extension (NBA 2K League team). In partnership with an NBA team and the affiliated NBA 2K esports team, a survey of 195 individuals assessed the brand extension on several variables, including extension awareness, perceived quality, image fit, categorical fit, innovativeness, and authenticity of the extension. Further, a cluster analysis revealed four distinct groups, (1) Gamers, (2) Traditional NBA Team Fans, (3) Crossover Fans, and (4) Low-Consumers. Discussion of the groups’ brand extension perceptions and behavior are highlighted. Targeted marketing for these clusters may improve efficiency of sports marketing messaging, as well as provide an understanding of the extension’s effect on the parent brand.
Keywords: Brand Equity; Brand Extension; Esport; Cluster Analysis; Market Segmentation